Revolutionizing Scientific Equipment Supply Chain through Standardization for Enhanced ESG Compliance: A Case Study on Spinco Biotech - Lingam, Dinakar; Jaffer, Dr. Syed (International Journal of Accounting and Economics Studies, 2025)
This research considers the important position that standardization initiatives hold in the supply chain of the pharmaceutical sector. It considers the challenges encountered and the increasing importance of adhering to Environmental, Social, and Governance (ESG) standards in this sector. The study illustrates how standardized approaches can be implemented to improve operational efficiency and maintain ethical governance. A thorough analysis of relevant research demonstrates how important it is for scientific equipment supply chains to be resilient, efficient, and multinational in their operation. It also shows how ESG compliance has evolved from a side concern to a crucial component of corporate strategy. Important insights into how standardization procedures might be integrated with operational effectiveness and ESG compliance can be gained from Spinco Biotech. This research validates the advantages of standardization on different supply chain activities, including distribution, inventory, logistics, and procurement, all of which contribute to business performance and ESG compliance. It also throws light on the difficulties that still exist, but also highlights the strategies that were created along the way. This study fills gaps in the literature base and calls for further intensive research in supply chain standardization and ESG compliance, thereby supporting sustainable development in the scientific equipment industry.
Keywords: Supply Chain Standardization; Scientific Equipment Industry; ESG Compliance; Operational Efficiency; Sustainability